Sequential hydrotalcite precipitation and biological sulfate reduction for acid mine drainage treatment. (August 2020) - Yan, Su; Cheng, Ka Yu; Morris, Christina; Douglas, Grant; Ginige, Maneesha P.; Zheng, Guanyu; Zhou, Lixiang; Kaksonen, Anna H.
Abstract: Hydrotalcite precipitation is a promising technology for the on-site treatment of acid mine drainage (AMD). This technology is underpinned by the synthesis of hydrotalcite that can effectively remove various contaminants. However, hydrotalcite precipitation has only limited capacity to facilitate sulfate removal from AMD. Therefore, the feasibility of coupling biological sulfate reduction with the hydrotalcite precipitation to maximize sulfate removal was evaluated in this study. AMD emanating from a gold mine (pH 4.3, sulfate 2000 mg L −1, with various metals including Al, Cd, Co, Cu, Fe, Mn, Ni, Zn) was first treated using the hydrotalcite precipitation. Subsequently, biological treatment of the post-hydrotalcite precipitation effluent was conducted in an ethanol-fed fluidized bed reactor (FBR) at a hydraulic retention time (HRT) of 0.8–1.6 day. The hydrotalcite precipitation readily neutralized the acidity of AMD and removed 10% of sulfate and over 99% of Al, Cd, Co, Cu, Fe, Mn, Ni, Zn. The overall sulfate removal increased to 73% with subsequent FBR treatment. Based on 454 pyrosequencing of 16S rRNA genes, the identified genera of sulfate-reducing bacteria (SRB) included Desulfovibrio, Desulfomicrobium and Desulfococcus . This study showed that sulfate-rich AMD can be effectively treated by integrating hydrotalcite precipitation and a biological sulfate reducing FBR. Graphical abstract: Image 1 Highlights: Hydrotalcite formation removed >99% metals and 10% sulfate from mine water. A subsequent bioreactor increased sulfate removal efficiency to 73%. Copper content of formed hydrotalcite was 2.2%, approaches ore grade. Dominant sulfate reducers were Desulfovibrio, Desulfomicrobium and Desulfococcus .